DNA Induces Conformational Changes in a Recombinant Human Minichromosome Maintenance Complex - Hesketh, Emma L. (J Biol Chem, 2015)
ATP-dependent DNA unwinding activity has been demonstrated for recombinant archaeal homohexameric minichromosome maintenance (MCM) complexes and their yeast heterohexameric counterparts, but in higher eukaryotes such as Drosophila, MCM-associated DNA helicase activity has been observed only in the context of a co-purified Cdc45-MCM-GINS complex. Here, we describe the production of the recombinant human MCM (hMCM) complex in Escherichia coli. This protein displays ATP hydrolysis activity and is capable of unwinding duplex DNA. Using single-particle asymmetric EM reconstruction, we demonstrate that recombinant hMCM forms a hexamer that undergoes a conformational change when bound to DNA. Recombinant hMCM produced without post-translational modifications is functional in vitro and provides an important tool for biochemical reconstitution of the human replicative helicase.